Mahmoud, Ali B. - (:unkn) unknown (My University, 2026)
A lecturer and researcher in business psychology, a cartoonist and a musician. Current research interests: Topics related to Consumer Behaviour, Work Psychology, Wartime Perceptions, and Research in Higher Education. Methods: Including but not limited to: Quantitative Multivariate Research, Thematic Analysis, and Mixed Methods. I'm open to any research collaborations. Please see the projects that I'm currently working on. https://www.researchgate.net/profile/Ali_Mahmoud https://www.researchgate.net/lab/Professor-William-D-Reisel-Lab-Ali-B-Mahmoud